Damerau Levenshtein Distance for Indonesian Spelling Correction - Puji Santoso; Pundhi Yuliawati; Ridwan Shalahuddin; Aji Prasetya Wibawa (Jurnal Informatika, 2019)
Word correction used to find an incorrect word in writing. Levenshtein distance is one of algorithm to correcting typing error. It is an algorithm that calculates a difference between two strings. The operations that used to the calculation are insert, delete, and substitution. However, this algorithm has a disadvantage that it cannot overcome two switched letters in the same word. The algorithm that can solve those issues is a damerau Levenshtein. This research aims to analyse a damerau Levenshtein algorithm that used to correcting Indonesian spelling. The dataset in this research consists of two fairy tale stories with a total of 1266 words and 100 typing errors. From these two algorithms, the accuracy is up to 73% on Levenshtein distance and 75% on damerau Levenshtein.